Cavitation bubble dynamics during pulsed laser ablation of a metallic glass in water. (February 2017) - Jiang, M.Q.; Wu, X.Q.; Wei, Y.P.; Wilde, G.; Dai, L.H.
Abstract: We report a cavitation bubble formation in water induced by nanosecond pulsed laser ablation of a Zr-based (Vitreloy 1) bulk metallic glass target. Only the first bubble occurs due to an explosive-boiling-type ablation of the target. A theoretical model is developed to quantitatively describe the bubble nucleation and its initial growth. The results demonstrate that the laser-induced plasma can induce the nucleation of the bubble. Furthermore, it is revealed that the initial bubble growth is approximately adiabatic and inertial, obeying the Rayleigh–Plesset theory, albeit the significant ablation. This work sheds insight into the mechanics of water-confined laser ablation of metallic glasses, and provides guidance for synthesizing amorphous nanoparticles. Graphical abstract: